Is the African Court’s decision in Dexter Eddie Johnson v Ghana a missed opportunity? A reply to Andrew Novak (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:This note is a reply to Andrew Novak’s commentary on the African Court’s ruling in Dexter Eddie Johnson v Ghana. Novak’s thesis is that the African Court missed an opportunity, by dismissing the application by Dexter Eddie Johnson, to join other courts that have declared the mandatory death penalty as being against international human rights law. In my reply, I argue that the Court did not miss any opportunity because the case before the Court did not provide the Court with an opportunity to pronounce itself on the substantive issues raised by the applicant. My main argument is that Novak makes an error by over-focussing on the potential merits of Dexter Eddie Johnson’s case, in determining that the Court missed an opportunity, when the case itself was preliminarily dismissed for inadmissibility. My conclusion is that the African Court correctly applied article 56(7) of the African Charter on Human and Peoples’ Rights in declaring the application inadmissible. TITRE ET RÉSUMÉ EN FRANCAIS:La décision de la Cour africaine dans Dexter Eddie Johnson c. Ghana est-elle une opportunite ratée? Une réponse à Andrew NovakRÉSUMÉ:Ce commentaire de decision est une réponse au commentaire d’Andrew Novak sur la décision de la Cour africaine dans l’affaire Dexter Eddie Johnson c. Ghana. La thèse de Novak est qu’en rejetant la demande de Dexter Eddie Johnson, la Cour africaine a manqué l’occasion de rejoindre d’autres juridictions qui ont décidé que la peine de mort obligatoire était en marge du droit international des droits de l’homme. Cette contribution soutient que la Cour n’a raté aucune opportunité, car l’affaire dont elle était saisie ne lui offrait pas l’occasion de se prononcer sur les questions de fond soulevées par le requérant. Mon principal argument est que Novak commet une erreur en se focalisant de manière indue aux potentielles questions de fond de l’affaire Johnson pour conclure que la Cour a raté une occasion, alors que l’affaire elle-même a été rejetée pour irrecevabilité. Le présent commentaire conclut que la Cour africaine a fait une application correcte de l’article 56(7) de la Charte africaine des droits de l’homme et des peuples en déclarant la requête irrecevable.
Keywords: African Court on Human and Peoples’ Rights; mandatory death penalty; admissibility; Ghana; Johnson v Ghana; res judicata